To Hell or the Pecos, a novel - Dearen, Patrick (Book collections on Project MUSE., 2012)
Tom Rowden has been riding away from the Pecos River for twenty years, plagued by the haunting image of his wife, Sarah, the second before he killed her. Now, he is dead-set on returning to her unmarked grave above the river to make one final atonement.